Osteoblast-Specific Overexpression of Nucleolar Protein NO66/RIOX1 in Mouse Embryos Leads to Osteoporosis in Adult Mice - Qin Chen; Krishna M. Sinha; Benoit de Crombrugghe; Ralf Krahe (Journal of Osteoporosis)
In previous study, we showed that nucleolar protein 66 (NO66) is a chromatin modifier and negatively regulates Osterix activity as well as mesenchymal progenitor differentiation. Genetic ablation of the NO66 (RIOX1) gene in cells of the Prx1-expressing mesenchymal lineage leads to acceleration of osteochondrogenic differentiation and a larger skeleton in adult mice, whereas mesenchyme-specific overexpression of NO66 inhibits osteochondrogenesis resulting in dwarfism and osteopenia. However, the impact of NO66 overexpression in cells of the osteoblast lineage in vivo remains largely undefined. Here, we generated osteoblast-specific transgenic mice overexpressing a FLAG-tagged NO66 transgene driven by the 2.3 kB alpha-1type I collagen (Col1a1) promoter. We found that overexpression of NO66 in cells of the osteoblast lineage did not cause overt defects in developmental bones but led to osteoporosis in the long bones of adult mice. This includes decreased bone volume (BV), bone volume density (bone volume/total volume, BV/TV), and bone mineral density (BMD) in cancellous compartment of long bones, along with the accumulation of fatty droplets in bone marrow. Ex vivo culture of the bone marrow mesenchymal stem/stromal cells (BMSCs) from adult Col1a1-NO66 transgenic mice showed an increase in adipogenesis and a decrease in osteogenesis. Taken together, these data demonstrate a crucial role for NO66 in adult bone formation and homeostasis. Our Col1a1-NO66 transgenic mice provide a novel animal model for the mechanistic and therapeutic study of NO66 in osteoporosis.